2016
DOI: 10.3390/su8101029
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Patterns in Convergence among High-Technology Industries: A Co-Occurrence-Based Analysis of Newspaper Article Data

Abstract: Firms in high-technology industries have faced great technological and market uncertainty and volatility in the past few decades. In order to be competitive and sustainable in this environment, firms have been pursuing technological innovation, product differentiation, vertical integration, and alliances, which eventually drive industry convergence, defined as the process of blurring boundaries between previously distinct industries. Although industry convergence has greatly affected industrial structure and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Based on this temporal classification of industry convergence, an opportunity to detect the actual step of industry convergence at a very early point in time is presented. This timeframe also contributes to the literature on the speed of industry convergence, such as the work by Lee et al (2016), which investigates Thirdly, convergence researchers urgently called for a suitable measure to assess and anticipate industry convergence (see e.g. Kim et al, 2018), which, up to now, mainly relied on technology convergence as an early indicator for a possibly upcoming industry convergence.…”
Section: Implications To Theorymentioning
confidence: 99%
“…Based on this temporal classification of industry convergence, an opportunity to detect the actual step of industry convergence at a very early point in time is presented. This timeframe also contributes to the literature on the speed of industry convergence, such as the work by Lee et al (2016), which investigates Thirdly, convergence researchers urgently called for a suitable measure to assess and anticipate industry convergence (see e.g. Kim et al, 2018), which, up to now, mainly relied on technology convergence as an early indicator for a possibly upcoming industry convergence.…”
Section: Implications To Theorymentioning
confidence: 99%
“…Firms are likely to suffer from obsolescence when they source all relevant knowledge within their organizational boundaries [32,33]. Particularly in today's business environment where a convergence of diverse inter-industry knowledge is important [34][35][36], exploitation relying exclusively on prior knowledge within a firm may result in a competitive disadvantage in the current market. Indeed, many firms are searching for and acquiring valuable knowledge through distant search beyond their industrial boundaries to ensure their current viability [18,37].…”
Section: Ambidexterity In Learningmentioning
confidence: 99%
“…Some scholars provided a more detailed analysis of the internal mechanism of promoting economic growth through the high-tech industry [15]. The growth of high-tech industries has a strong multiplier effect on driving the development of related industries [16] and accelerates the rapid growth of the national economy. Some researchers described the relationship from the perspective of industrial R&D [17,18] by establishing the endogenous economic growth model based on R&D and reported that technological progress was the endogenous source of long-term economic growth.…”
Section: Introductionmentioning
confidence: 99%